Transvaginal natural orifice specimen extraction surgery in simple nephrectomy - Jeena R. Kudunthail; Kartik Sharma; Deepak Prakash Bhirud; Mahendra Singh; Gautam Ram Choudhary; Shiv Charan Navriya; Arjun Singh Sandhu (Indian Journal of Urology)
Introduction: Natural orifice specimen extraction surgery (NOSES), particularly transvaginal NOSES, is an innovative approach in laparoscopic urological surgery. This study aims to assess the feasibility, safety, and outcomes of transvaginal NOSES in women undergoing laparoscopic simple nephrectomy in an Indian cohort. Methods: A prospective observational study was conducted from September 2022 to May 2024 in the department of urology, including 15 women with prior vaginal deliveries undergoing simple nephrectomy. Exclusion criteria were vaginal scarring, previous pelvic surgeries, active intravaginal infections, cervical neoplasia, unresolved pelvic inflammation, and patient refusal. Parameters assessed included operative time, specimen extraction time, blood loss, postoperative recovery metrics, Female Sexual Function Index, and Pelvic Floor Impact Questionnaire scores at the baseline and at 3 months. Results: The mean age of the patients was 45.73 years. The average operative time, including the specimen extraction was 127.8 min and the average extraction time was 30.13 min. None required conversion to open surgery, and the average blood loss was 68.0 mL with no intraoperative transfusions. The postoperative recovery was rapid, with milestones achieved within 1 day, and the average hospital stay was 2.2 days. Pain scores were low (Visual Analog Scale: 2.87 at 24 h and 1.47 at 48 h). The complication rate was 6.67%, with one case of vaginal bleeding which was managed conservatively. Postoperative pelvic floor and sexual functions were preserved without significant adverse effects. Conclusion: Transvaginal NOSES is a feasible and safe technique for nephrectomy, offering reduced postoperative pain, minimal blood loss, and rapid recovery, enhancing surgical outcomes and patient satisfaction.